at the Directorate General of Teachers and Educational Personnel Ministry of Education, Culture, Research and Technology - Asrul Sani, Aswin; Rivai Zainal, Veithzal; Hakim, Azis (Journal of Economics and Business UBS, 2023)
Public services are an important task that cannot be ignored by local governments, because if the service component stagnates, it is almost certain that all sectors will be affected. Therefore, there needs to be good planning and even need to formulate service standards for the community in accordance with the authority given by the central government to regional governments. One of the service improvements that needs to be carried out by local governments is improving services in the education sector. This research was carried out at the Directorate General of Teachers and Education Personnel. In this research, it was carried out using qualitative descriptive research, namely describing the condition of the object to be studied. Descriptive research obtains a systematic, factual and accurate picture of the facts, characteristics and relationships between the phenomena being investigated. In this research, the object to be studied is the implementation of service quality in the field of education at the Directorate General of Teachers and Education Personnel. Data collection techniques in this research were observation, interviews and documentation. Human qualities in an agency are realized by the employees themselves in carrying out their daily tasks, such as loyalty to the agency, relationships with customers, cooperation with other employees, group work experience, cooperative relationships between work units, and commitment to realizing strategic decisions. By realizing good quality human resources in their daily tasks, agencies can have intangible assets that have influence. The Directorate General of Teachers and Education Personnel must maintain or further improve the quality of service provided by the Directorate General of Teachers and Education Personnel by establishing good relations between fellow employees, superiors and subordinates and vice versa.